Cytomorphological traits of fine-needle aspirates of hyalinizing trabecular tumor of the thyroid gland: A brief report - Fei Wang; Yufei Liu (Indian Journal of Pathology and Microbiology)
Background: The incidence of thyroid tumor is increasing, and preoperative diagnosis of hyalinizing trabecular tumor (HTT) is difficult. Aim: To investigate the cytological features of HTT of the thyroid gland. Settings and Design: A retrospective observational study. Materials and Methods: Ultrasonography, preoperative needle aspiration cytology, postoperative histopathology, immunohistochemistry, and BRAF V600E gene test were performed in five patients with HTT to analyze the pathological characteristics of the patients and review the relevant literature. Results: Four female and one male patients with HTT were recruited. Fine-needle aspiration cytology (FNAC) showed bloodstained background tumor cells with multiple morphologies. The tumor cells exhibited ovoid nuclei, abundant cytoplasm, fine chromatin, nuclear crowding and overlapping, and small nucleoli. Focal nuclear pseudoinclusions and grooves were present. No papillary structures or psammoma bodies were observed. In all cases, tumor cells were radially distributed around the eosinophilic extracellular matrix. In 40% (2 in 5) of cases, trabecular patterns of elongated tumor cells were present, with their nuclei staggered along the longitudinal axis of tumor cells in the trabeculae. FNAC suggested two cases of HTT and three cases of papillary thyroid cancer. Post-operational biopsy indicated they were HTT cases. Conclusion: HTT is a rare thyroid tumor with non-specific clinical manifestations. It can be misinterpreted as papillary thyroid carcinoma by FNAC. However, its cytomorphological traits are helpful in the diagnosis. In combination with FNAC, immunohistochemistry, and molecular testing, HTT can be accurately diagnosed.